Rancangan Tempatan Majlis Daerah Yan, Kedah 2035, Penggantian: Jilid 1 Pernyataan Bertulis dan Peta Cadangan - Shamsudin@ Sani, Zaliah; Jaafar, Mohamad Nazri; Abdul Ghani, Aisyah Afiqah; Yahya, Mohammad Zaki; Mohamad nazri, Fatin Nadhrah; Mahmud, Khairil; Abdul Razak, Zainal; Asmawi, M. Zainora (Jabatan Perancangan Bandar dan Desa Negeri Kedah (PLANMalaysia Kedah), 2024)
The Yan District Council Local Plan, Kedah 2035 (P) is prepared in accordance with the Town and Country Planning Act 1976 (Act 172) for the Amendment, Cancellation, or Replacement of a Local Plan. This plan replaces the expired Yan District Local Plan 2020 (RTD Yan 2020) and covers physical, environmental, and agricultural sectors.